Cardiac cystic echinococcosis-A systematic review and analysis of the literature. - Simone Bumann; Esther Kuenzli; Raffaella Lissandrin; Enrico Brunetti; Sam Goblirsch; Lars Henning; Francesca Tamarozzi; Andreas Neumayr (Public Library of Science (PLoS), 2024)
Human cystic echinococcosis (CE) is a parasitic infection caused by the larval stage of the tapeworm Echinococcus granulosus sensu lato, primarily affecting the liver and lungs. Although the heart is affected in only 0.02-2% of all CE cases, a considerable number of cases have been, and continue to be, published. However, due to the rare occurrence of cardiac CE and the resulting lack of clinical trials, knowledge about various aspects of the disease remains limited. To obtain a clearer picture of anatomical, clinical, diagnostic as well as therapeutic aspects of cardiac CE, we systematically reviewed the literature published between 1965 and 2022. The anatomical pattern of the affected cardiac structures follows the extension of the supplying capillary bed. The majority of patients (82.7%) are symptomatic and present with prolonged non-specific symptoms such as dyspnoea, chest pain and palpitations. Acute complications generally derive from cyst rupture, occur in 18.3% of cases and manifest as embolism, pericardial tamponade, or anaphylactic reaction in 83.2%, 17.8% and 10.9% of these cases, respectively. As for CE cysts localized in other organs, the diagnosis of cardiac CE is made by imaging. Serology plays a minor role due to its limited sensitivity. Unlike abdominal CE cysts, cardiac CE cysts are usually resected independent of their stage (active/inactive), because their presence impairs cardiac performance and carries the risk of long-term sequelae. More than 80% of patients are treated with a single surgical intervention. We found a disease-related case fatality rate of 11.1%. Since local recurrence was reported up to 108 months and secondary CE up to 72 months after surgery, patients should be followed up for a minimum of 10 years.